Smartphone-based colorimetric detection of cardiac troponin T via label-free aptasensing - Ulloa-Gomez, Ana M.; Agredo, Alejandra; Lucas, Alec; Somvanshi, Sandeep B.; Stanciu, Lia (Biosensors & bioelectronics, 2023)
We report an aptasensing platform for the detection of cardiac troponin T (cTnT) in the immediate and early phases of acute myocardial infarction (AMI). High-flow filter paper was used to fabricate a microfluidic paper-based analytical device (μ-PAD), which was further modified with gold-decorated polystyrene microparticles functionalized with a highly specific cTnT aptamer. Herein, cTnT detection is presented in two linear ranges (0.01-0.8 μg/ml and 6.25-50 μg/ml) with an LoD of 3.9X10−4 μg/ml, which is in agreement with reference values determined by the American Heart Association. The proposed platform showed remarkable selectivity against AMI-associated cardiac biomarkers such as TNF-alpha, interleukin-6, cardiac troponin I, and reactive protein-C. This aptasensor is a label-free assay that relies only on smartphone-based image analysis and takes less processing time in comparison with traditional methods like ELISA. Furthermore, it exhibits outstanding stability over 23 days when devices are stored at 4 °C. The reported platform is a stable and cost-effective method for the on-site and user-friendly detection of cTnT in normal saline buffer and diluted human serum.